Fillers and Hedges in Mrs. Tri Risma Maharini’s Speeches - Muhayyang, Maemuna; Armas, Muhammad Fakhrul (ELT Worldwide: Journal of English Language Teaching, 2025)
Women differ in the linguistic features they use, and Lakoff’s theory has served as a foundation for subsequent researchers to distinguish between women’s and men’s language. This study explores the use of fillers and hedges in the speeches of Mrs. Tri Risma Maharini, drawing on Lakoff’s foundational theory to examine gendered language differences. The primary objective is to identify the types and functions of fillers and hedges employed in her speeches. To analyze fillers, Rose’s (1998) typology is combined with insights from Stenström (1994) and Baalen (2001), while the classification of hedges and their functions is based on Salager-Mayer’s (1995) framework. A descriptive qualitative approach, using discourse analysis, was employed to investigate the data. The findings aim to highlight the types and functions of fillers and raise awareness among learners about their use during moments of hesitation in foreign language communication—an inherent aspect of spoken language. Additionally, the study underscores the role of hedges in signaling sensitivity to others’ feelings, suggesting that hedging expressions contribute to a more empathetic and contextually aware exchange.